Pengaruh Struktur Kepemilikan, Tangibility, Firm Age, Business Risk, Kebijakan Dividen, dan Sales Growth terhadap Struktur Modal Perusahaan Sektor Properti Real Estate yang terdaftar di BEI tahun 2012-2016 - DWI CAHYANI, INTAN; ISBANAH, YUYUN (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract The availability of capital resources is very important in nature and is a mandatory requirement of the company. The purpose of this research is to analyze the influence of ownership structure, tangebility, firm age, business risk, dividend policy, and sales growth on capital structure of real estate property sector registered in 2012-2016. This type of research is quantitative research. This study uses secondary data in the form of annual report on IDX. Pursuant to purposive sampling method, 13 companies used as sample. The results of this study indicate that tangebility and buiness risk affect the capital structure. While the ownership structure, firm age, dividend policy, and sales growth have no effect on the capital structure. Keywords: capital structure, ownership structure, tangibility, firm age, business risk.